Pediatric Thrombolysis: A Practical Approach - Tarango, Cristina; Manco-Johnson, Marilyn J. (Frontiers in Pediatrics, 2017)
The incidence of pediatric venous thromboembolic disease is increasing in hospitalized children. While the mainstay of treatment of pediatric thrombosis is anticoagulation, reports on the use of systemic thrombolysis, endovascular thrombolysis, and mechanical thrombectomy have steadily been increasing in this population. Thrombolysis is indicated in the setting life- or limb-threatening thrombosis. Thrombolysis can rapidly improve venous patency thereby quickly ameliorating acute signs and symptoms of thrombosis and may improve long-term outcomes such as post-thrombotic syndrome. Systemic and endovascular thrombolysis can result in an increase in minor bleeding in pediatric patients, compared with anticoagulation alone, and major bleeding events is a continued concern. Also, endovascular treatment is invasive and requires technical expertise by interventional radiology or vascular surgery, and such expertise may be lacking at many pediatric centers. The goal of this mini-review is to summarize the current state of knowledge of thrombolysis/thrombectomy techniques, benefits, and challenges in pediatric thrombosis.